In situ conservation of plant genetic resources in home gardens of southern Vietnam: A report of home garden surveys in southern Vietnam, December 1996-May 1997 - Hodel, U.; Gessler, M.; International Plant Genetic Resources Institute (1999)
This field study examined fundamental questions about the role of home gardens in conservation, namely how the dynamic nature and mutliple uses of home gardens affect the stability of this micro-system and its role as a viable conservation unit. The results presented here should contribute to the development of complementary in situ conservation strategies and methods that take account of and include micro-environments such as home gardens which are used, valued and dynamic.